2019
DOI: 10.3847/1538-3881/aaf1b1
|View full text |Cite
|
Sign up to set email alerts
|

A Second Terrestrial Planet Orbiting the Nearby M Dwarf LHS 1140

Abstract: LHS 1140 is a nearby mid-M dwarf known to host a temperate rocky super-Earth (LHS 1140 b) on a 24.737-day orbit. Based on photometric observations by MEarth and Spitzer as well as Doppler spectroscopy from HARPS, we report the discovery of 2 Ment et al.an additional transiting rocky companion (LHS 1140 c) with a mass of 1.81 ± 0.39 M ⊕ and a radius of 1.282 ± 0.024 R ⊕ on a tighter, 3.77795-day orbit. We also obtain more precise estimates of the mass and radius of LHS 1140 b to be 6.98 ± 0.89 M ⊕ and 1.727 ± 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 65 publications
6
124
2
Order By: Relevance
“…We analysed the spin and orbit evolution of the system by considering that the two planets have a small value of the relaxation factor (which is consistent with the discussions presented in Dittmann et al (2017) and Ment et al (2019) regarding the planets compositions and internal structure models). The results of the numerical experiments have shown that the eccentricity decay of both planets is ruled by the eccentricity decay of the inner planet.…”
Section: Spin-orbit Evolutionsupporting
confidence: 71%
See 3 more Smart Citations
“…We analysed the spin and orbit evolution of the system by considering that the two planets have a small value of the relaxation factor (which is consistent with the discussions presented in Dittmann et al (2017) and Ment et al (2019) regarding the planets compositions and internal structure models). The results of the numerical experiments have shown that the eccentricity decay of both planets is ruled by the eccentricity decay of the inner planet.…”
Section: Spin-orbit Evolutionsupporting
confidence: 71%
“…The results of Fig. 1 show that, if the eccentricities of LHS-1140 b and c are close to the upper boundary values estimated by Ment et al (2019), the rotation of the planets is most likely not synchronous if we suppose that the planets had a past fast rotation rate with Ω n.…”
Section: Spin-orbit Resonancesmentioning
confidence: 58%
See 2 more Smart Citations
“…The SPOC simple aperture photometry (SAP) and presearch data conditioned (PDCSAP) light curves (Smith et al 2012;Stumpe et al 2014) of L 98-59 are shown in Figure 1. We use the methods appropriate for M dwarfs previously used by Berta-Thompson et al (2015), Dittmann et al (2017), and Ment et al (2019) to determine the stellar parameters of the host star, and adopt these parameters throughout our analysis. We estimate the mass of the star using the mass-luminosity relation in the K band from Benedict et al (2016) to be 0.313±0.014 M e .…”
Section: Introductionmentioning
confidence: 99%